Analysis of cardiac exams: electrocardiogram and echocardiogram use In Duchenne muscular dystrophies - Cynthia Kallás Bachur; Marlon Hermógenes Garcia; Camila Araújo Bernardino; Rogério Camillo Requel; José Alexandre Bachur
Introduction Duchenne Muscular Dystrophies (DMD) is a genetic muscle disorder that causes degeneration and atrophy of skeletal muscle and heart. Objective The aim of this survey is accomplish an evaluation electrocardiographic and echocardiography in the patients bearers of Duchene Muscular Dystrophies (DMD), to observe which alterations, which the degree of cardiac compromising these patient present and the effectiveness of these exams in the evaluation cardiologic. Methods Nine patients of the sex male bearers of DMD, with medium age of 14.12 ± 4.19 years, varying of 7 to 23 years were appraised. All were submitted to the evaluation physiotherapy and the cardiologic: electrocardiogram and echocardiogram. Results The experimental conditions of the present survey we propitiate the observation of the alterations echocardiography, as well as: significant increase in the diastolic diameter of the left ventricular (LV), increase in the systolic diameter of the left atrium (LA), and significant decrease of the ejection fraction of the LV, characterizing global systolic function reduced, and of the alterations electrocardiographic suggested possible overload of RV, septum hypertrophy, blockade of left previous fascicle and overload of atrium left. Compatible alterations of hypertrophy left ventricular were not observed. Conclusion The evidences corroborate with the data described in the literature in the characterization of an important heart compromising that these patient present, like this the evaluation cardiologic, through the complemented exams of the echocardiography and electrocardiography provide important information for the prognostic, the accompaniment, and the treatment of patient bearers of DMD.